The Development of Self Help Book for Counseling Guidance’s Teacher Experiencing Burnout Symptoms with Counseling Cognitive Behavioral Therapy - Rizanty, Rahmadhania; Fridani, Lara; Marjo, Happy Karlina (Universitas Malikussaleh, 2021)
Self help book is believed as an alternative method to help someone in order to help himself dealing with the psychological problems that they had experienced. One of the psychological problems which very vulnerable to be experienced by someone that working is emersion of burnout symptoms. The researcher has interviewed Counseling Guidance’s (BK) teacher to find the factor that caused emersion of burnout symptoms of work, from the interview some informations has gathered about the causes of Counseling Guidance's teacher experienced burnout symptoms, among others because the number of Counseling Guidance teachers in the school with an unbalanced number of students and unclear duties and roles assigned to Counseling Guidance teachers. Other that, there were many Counseling Guidance teachers did not have an appropriate knowledge with the qualification that have been determined. Every individual has a different level of burnout symptoms and the impact that they experienced was also different. The level of burnout symptoms could be reduced or even eliminated by determining the appropriate method, one of them by counseling approach of Cognitive Behaviour Therapy (CBT) using guided imagery technique.